Modernisasi Agama Di Indonesia - Syah, Irman; Amalia, Putri; Anugrah, Anugrah (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This article discusses the diverse concept of moderation in various contexts, from its definition and basic values ​​to its implementation in Indonesia. Moderation, which comes from the Latin "moderâtio," means balance and avoidance of extremism. In Islam, this concept is known as wasathiyyah, which reflects tolerance, justice and balance. This article also explains how religious moderation is implemented in Indonesia through various government and community efforts, such as internalizing religious values, strengthening state commitment, socializing religious moderation, inter-religious cooperation, and efforts to maintain national unity. The role of social media in disseminating diverse understandings of moderation is also discussed, underscoring the importance of digital platforms in shaping the mindset of a more tolerant and inclusive society.